Usefulness of different DTI parameters in identifying neurodegenerative process: Evidence from amyotrophic lateral sclerosis. (September 2016) - Karavasilis, E.; Christidi, F.; Toulas, P.; Efstathopoulos, P.E.; Rentzos, M.; Zouvelou, V.; Xirou, S.; Evdokimidis, I.; Kelekis, L.N.
Abstract : Introduction: Diffusion Tensor Imaging (DTI) reveals in vivo abnormalities in white matter (WM) fiber structure and has improved our knowledge of disease pathophysiology in several central nervous system (CNS) pathologies with WM involvement, especially through the analysis of different DTI indices. Purpose: To investigate the sensitivity of DTI parameters using tract based spatial statistics (TBSS) in amyotrophic lateral sclerosis (ALS), as a CNS disease with predominant WM involvement. Material and methods: We included 58 participants (36 patients with ALS and 22 healthy controls). All of them were scanned on 3.0T MR system, with 30-directional DTI and 3D-T1-weighted anatomical sequences. Whole-brain WM analysis was conducted using FSL and TBSS to estimate fractional anisotropy (FA), axial diffusivity (Ad) and radial diffusivity (Rd). Voxelwise statistical analysis was performed via a permutation-based inference for nonparametric statistical thresholding (5000 permutations). Two sample t -tests were applied to evaluate local alterations in DTI parameters ( p  < 0.05 with family-wise error correction for multiple comparisons). Results: In ALS patients we observed significant decreased FA and increased Rd ( p  < 0.05) in several WM areas (right > left), including corticospinal tract (CST), body of the corpus callosum and superior longitudinal fasciculus. Rd changes were more diffuse and found along the CST axis (WM of precentral gyrus, corona radiata, internal capsule). No changes were detected for Ad ( p  > 0.05). Conclusion: Decomposing the commonly used DTI parameters (FA and Mean Diffusivity) into Ad and Rd may be useful in identifying widespread WM changes in ALS and proved as a potential sensitive index for CNS neurodegenerative process. Disclosure: F.C. acknowledges support from theIKY Fellowships of Excellence for Postgraduate Studies in Greece – Siemens Program . We also acknowledge the Philips Medical System for providing all necessary research keys for MR/DTI sequence acquisition. The funders and/or contributors had no role in study design, data collection and analysis or preparation of the abstract. Finally, we would like to thank the patients with ALS and their families, as well as healthy volunteers for their willingness to participate to the present study.